2012
DOI: 10.1111/j.1440-1746.2012.07123.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin protects obese mice against hepatic ischemia–reperfusion injury by Toll‐like receptor‐4 suppression and endothelial nitric oxide synthase activation

Abstract: Statins exert major hepatoprotection against IRI in lean, fatty, and NASH livers that is not due to cholesterol removal. Rather, statins downregulate TLR4 to prevent NF-κB activation, with resultant suppression of adhesion molecules, chemokines/cytokines, and thromboxane B2 production. Short-term statin treatment is an effective, readily-available preventive agent against hepatic IRI, irrespective of obesity and fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
(114 reference statements)
2
22
1
Order By: Relevance
“…Moreover, the observed increase in NO may be an adaptive response of the injured liver. Ajamieh et al (2012) found that there were increases in NOS3 levels and NOS3 phosphorylations after liver injury in NASH, and they were found to be protective against NASH. Based on these observations, we argued that though NO is considered proinflammatory and an M1 marker, the kinetics of NO release and its concentration in the hepatic microenvironment might play an adaptive and perhaps a protective role in the pathophysiology of NASH.…”
Section: No Donor Attenuates Inflammation In Nash Livermentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the observed increase in NO may be an adaptive response of the injured liver. Ajamieh et al (2012) found that there were increases in NOS3 levels and NOS3 phosphorylations after liver injury in NASH, and they were found to be protective against NASH. Based on these observations, we argued that though NO is considered proinflammatory and an M1 marker, the kinetics of NO release and its concentration in the hepatic microenvironment might play an adaptive and perhaps a protective role in the pathophysiology of NASH.…”
Section: No Donor Attenuates Inflammation In Nash Livermentioning
confidence: 99%
“…NO, released from any of the three NOS upon their activation, plays a significant role in inflammation (Fujita et al, 2010;Ajamieh et al, 2012). However, the inducible form of the NOS has been ascribed to the proinflammatory phenotype more often (Fujita et al, 2010;Maina et al, 2012).…”
Section: No Donor Attenuates Inflammation In Nash Livermentioning
confidence: 99%
See 2 more Smart Citations
“…9 The study from Ajamieh and colleagues published this month in the Journal of Gastroenterology and Hepatology provides new and important concepts regarding the use of statins as prophylactic agents to prevent warm I/R injury in the liver. 10 This study, conducted in experimental models of non-alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH), demonstrated that oral administration of atorvastatin for 10 days prior to warm I/R injury markedly prevented hepatocellular damage. Although readers might now think that the herein published study represents a reiteration of the Llacuna study, it is not.…”
mentioning
confidence: 99%